DEVELOPMENT OF DTLPLP FOR LINK PREDICTION ON DYNAMIC HETEROGENEOUS NETWORK USING HETER-LP APPROACH - Hemsa Ghaida, Radhinansyah
Link prediction is a method to see the possibility of a link in a complex network based on the previously formed network. However, until now the link prediction method has only been developed for heterogeneous or dynamic cases. In fact, most real cases can be described with heterogeneous and dynamic networks. The implementation of this thesis is carried out to carry out the development of the DTPLLP method which can